Tattoos among athletes: a matter of concern? - Kluger, N. (The Journal of Sports Medicine and Physical Fitness, 2021)
Ten to 30% of the population is currently tattooed. This trend does not spare athletes and sports medicine specialists may have to manage tattooed athletes. The purpose of this study was to review the possible issues associated with tattoos among athletes. Overall, tattooed athletes are exposed to the same complications as anyone, mainly healing issues, skin infections and allergic reactions to a tattoo color. Besides, the main pitfall in sports medicine remains invasive gestures such as puncture or infiltration, as they must be avoided at all cost if the tattoo is recent and under healing. Issues associated with imaging are rather limited (artifacts, visible calcification). Burns during magnetic resonance imagining may occur but they are rather rare. Local neuromuscular complications attributable to tattooing are exceptional. Whether tattoos may have a "systemic" impact on the prevalence of unexplained symptoms in athletes (fatigue, distant tendon or musculoskeletal wounds) remain unknown.